A study on tool wear in ultra-precision diamond turning with finite element modelling. (1st January 2011) - Wang, H.; To, S.
As one of the most effective numerical modelling methods, finite element method (FEM) has been developed to study the tool wear in all kinds of machining processes. The widely adopted static 2D/3D FEM models are capable of modelling the steady state of continuous cutting process; however, these models in nature cannot explain the mechanism of tool wear in ultra-precision diamond turning due to the lack of consideration of the fundamental physical phenomena of tool-tip vibration in the micro-cutting process. In this paper, the relative tool-work displacement induced by tool-tip vibration is considered in the finite element modelling to study the tool wear in diamond turning of non-ferrous materials. The simulation results of the geometry of worn tools are consistent with the experimental data.